INTEGRATION OF THE CONTENT OF ECONOMIC CULTURE INTO THE PROFESSIONAL TRAINING OF FUTURE TECHNICIANS OF TRANSPORT TECHNOLOGIES AND TRANSPORT MANAGEMENT IN ROAD TRANSPORT (Innovative professional education, 2024)
The highlights the main methodological approaches to combining economic knowledge with technical disciplines, in particular through an interdisciplinary approach, project-oriented learning and the use of case method. Attention is focused on the fact that theintegration of economic culture in the professional training of future technicians of transport technologies and management of transportation by road transport in the context of modern sustainable development is possible if number of conditions are met, including pedagogical ones. The importance of implementing digital technologies and person-oriented models in the transport sector is also outlined and business collaborations and public-private partnerships that provide students with access to up-to-date knowledge and tools used in industry.
Keywords: public-private partnership, interdisciplinary approach, integration, economic culture, case method, sustainable development, transport industry